Переписка с О. А. Бредиус-Субботиной. Неизвестные редакции произведений (2006)
Имен. указ.: с. 1041-1051 Экземпляры: ФИЛ (20060525) / Инвентарный номер: 1061044 / Цена: 78.00 / Сис.шифр: 83.3(2=Рус)1-8 / Авт.знак: Ш 72 / ГРНТИ: 17 / ББК: 83.3(2=Рус)1-8